Joint creation standards across CRPs and Platforms - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The CCAFS knowledge management team brought together 12 CRPs and 4 Platforms to define and agree on common standards to be used for planning, reporting and program management. These joint efforts led to the adoption of the MARLO tool at the system level, i.e, System Management Office. For CCAFS alone, MARLO helped CCAFS track donor investment, allowing greater transparency and tracking of resources.